2014
DOI: 10.1007/s12517-014-1486-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrated geophysical and physicochemical assessment of Olushosun sanitary landfill site, southwest Nigeria

Abstract: An integrated surface geophysical and physicochemical study involving 2-D electrical resistivity imaging (terrain conductivity measurement using EM34-3) complimented with measurement of some physical parameters was conducted at Olushosun sanitary landfill site in Lagos metropolis, southwestern Nigeria, with the aim of investigating the lateral extent and depth of the possible subsurface leachate contamination plumes (electrically conductive anomalies) within the area. Fourteen 2-D resistivity imaging lines wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The uncontrolled disposal of lead acid batteries and spent petroleum products probably caused relatively higher levels of Pb, Cu and Fe found in groundwater around the study area (Oyeku and Eludoyin 2010). Also, statistical analyses of physical parameters determined in situ on groundwater from the work of Ayolabi et al (2014) around the dumpsite showed elevated concentrations of total dissolved solid, electrical conductivity, temperature and high acidic content. They concluded that the high level of pollution has been accelerated by the weak protective capacity of the thick laterite delineated within the study area.…”
Section: Introductionmentioning
confidence: 99%
“…The uncontrolled disposal of lead acid batteries and spent petroleum products probably caused relatively higher levels of Pb, Cu and Fe found in groundwater around the study area (Oyeku and Eludoyin 2010). Also, statistical analyses of physical parameters determined in situ on groundwater from the work of Ayolabi et al (2014) around the dumpsite showed elevated concentrations of total dissolved solid, electrical conductivity, temperature and high acidic content. They concluded that the high level of pollution has been accelerated by the weak protective capacity of the thick laterite delineated within the study area.…”
Section: Introductionmentioning
confidence: 99%
“…The Dahomey Basin is a combination of inland/coastal/offshore basin that stretches from southeastern Ghana through Togo and the Republic of Benin to southwestern Nigeria (Electronic Supplementary Material). Exposed geological formation reveals that the lithological units are mainly of sands, clays, their intercalations and limestone [6]. Several notable researchers have described the stratigraphy of the Dahomey Basin particularly southwestern part of Nigeria where the study lies to consist of Abeokuta group (Ise, Afowo and Araromi Formations), Ewekoro, Oshosun, and Ilaro Formations and Benin formation (coastal plain sands) [7].…”
Section: The Study Areamentioning
confidence: 99%
“…The migration of the leachate plume can also pollute the aquifers and surface waters over a long duration consequently leading to serious health and environmental risks [28]. The cheap mode of disposal of huge refuse in Lagos over the years is worrisome because it reduces the potential sources of potable water for the growing population [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations